Parametric study on volume fraction of Representative Volume Element (RVE) CFRP AND GFRP towards tensile properties - Ab Ghani, Ahmad Fuad; Ramli, Mohd Irman; Jumaidin, Ridhwan; Dhar Malingam, Sivakumar; Abdul Munir, Fudhail; Yob, Mohd Shukri (Penerbit Universiti Sultan Zainal Abidin, 2020)
The study of Representative Volume Element (RVE) on Composite Material has been performed in the aim to obtain the relation and effect of fiber volume fraction on its tensile properties which is one of the important mechanical properties for composite designers in automotive and aerospace community. The properties such as fibre content, orientation, dimension of constituent fibres (diameter), level of intermixing of fibres, interface bonding between fibre and matrix, and arrangement of fibres between different types of fibres, influences the mechanical properties of hybrid composite. Representative Volume Element (RVE) for each constituent Carbon Fiber Reinforced Polymer (CFRP)and Glass Fiber Reinforced Polymer (GFRP)assumed isotropic behavior for carbon fibre, glass fibre and epoxy resin matrix and assumed to be perfectly bonded interface between fibre and matrix region i.e. strain compatibility at the interface. The scope of study on the micromechanical modelling via representative volume element (RVE) is limited only to unidirectional composites. The result of parametric study performed deduces that incremental volume fraction of carbon and glass respectively will increase the E11(Modulus of Elasticity in Tensile Direction) and enhance the tensile properties of both CFRP and GFRP.